Biological maturity but not relative age biases exist in female international youth soccer players relative to the general population - Sweeney, Liam; Lundberg, Tommy R; Sweeney, Cian; Hickey, Jack; MacNamara, Áine (Biology of Sport, 2025)
This study investigated the extent to which biological maturity and relative age biases existed and varied with chronological age in female international youth soccer players relative to the general population. A total of 113 players (52 under-15 (U15), 32 under-16 (U16) and 29 under-17 (U17)) selected by the Football Association of Ireland participated in this study. All players were assessed for height, body weight and relative age. Biological maturity status and timing were assessed in U15 and U16 players only. Relative to population norms, the results showed a significant but small bias in favour of more biologically mature players ( P < 0.001, d = 0.39) that increased with age from U15 ( P = 0.007, d = 0.36) to U16 ( P = 0.009, d = 0.44). U16 players had achieved a significantly higher percentage of their predicted adult height than U15 players ( T = 7.4, P < 0.001). However, there were no relative age biases at any age group nor across the total sample ( P > 0.05). There was no significant difference in height, weight or relative age of the players between the three age groups and no significant difference between the U15 and U16 age groups in terms of predicted adult height or biological to chronological age offset. This study demonstrates that biological maturity but not relative age biases exist in female international youth football relative to the general population, with notable differences in pattern and magnitude compared to those previously observed in male international youth football.